OPEN SYSTEM ULTRASONIC NON-DESTRUCTIVE TESTING FOR QUALITY CONTROL FABRICATION OF LEAD-BRICK - RADIATION SHIELDING - Hijazi, Rhakamerta
There is a significant risk associated with the use of nuclear technology for health purposes. To minimize the risks from such use, a radiation shield must be employed to block excess radiation. One commonly used type of radiation shield is lead bricks because they are inexpensive and easily obtainable. The National Nuclear Energy Agency (BATAN), now known as the National Research and Innovation Agency (ORTN-BRIN), has the authority to ensure that lead bricks can effectively block radiation to guarantee the safety of people around nuclear treatment facilities. However, the production of lead bricks in Indonesia is still at the laboratory scale with conventional methods. This raises questions about the quality of the fabricated lead bricks. Additionally, periodic checks of installed lead bricks are only required once during the initial installation, which adds to doubts about the lead bricks' ability to block radiation. This is because the main inspection method, a leakage test using radioactive sources, is difficult to perform repeatedly. Therefore, a non-destructive ultrasonic testing method, which is relatively safer and easier to perform, is proposed as a supplement to support the primary testing method. Non-destructive testing using ultrasonic methods is commonly used for inspecting metal-based materials such as iron, steel, or aluminum, and even concrete. However, for lead-based materials, literature on using ultrasonics as a basis for non-destructive testing is very difficult to find. Thus, there is a need to develop an ultrasonic-based non-destructive testing system for radiation shields made of lead bricks. Several adjustments to ultrasonic parameters used for iron or steel need to be applied to lead material. The use of the un0rick open-source pulse generator and data acquisition device is crucial because of its flexibility in changing ultrasonic parameters. Moreover, the uneven surface of lead bricks can cause varying scanning angles. To accommodate this issue, the Partial Immersion Technique (PIT) method is used in this study. In this study, an ultrasonic-based non-destructive testing system using A-mode signal analysis and B-mode imaging is employed to evaluate lead brick samples. There are three lead brick samples representing three test scenarios. The first sample is a standard lead brick without any defects. This lead brick is used as a reference for testing other lead brick samples. The second sample is a lead brick with artificial holes to represent crack defects due to natural disasters when installed. Crack defects are crucial to evaluate because they can reduce the mechanical strength of a lead brick. The third sample is a lead brick with natural defects due to imperfect solidification processes. This sample represents the condition of fabrication errors where the cooling process during solidification should be done gradually. In A-mode signal analysis, the cross-correlation method is used as a basic method for comparing the quality of a product by comparing it with a standard test. In the first scenario, the standard sample will be compared with itself. The test results in the first scenario show that the average correlation of lead brick 1 for each point is 0.9426, the median is 0.9454, the standard deviation is 0.0241, and the worst correlation peak value is 0.8966. It can be said that all points of lead brick 1 have a similarity of up to 94.26% with a difference of about 2.41%. In the second scenario, with the basis of time lag, defects can be detected at depths of 13 mm, 23 mm, 28 mm, and 37 mm. In the third scenario, defects are detected at a depth of 37 mm. In B-mode image analysis, the image reconstruction method used is two-point interpolation. This method is commonly used because it is easy to calculate, but the drawback of this method is the appearance of fog-like noise due to the degradation of each point value. The use of image dehazing methods can be applied to remove the noise. In the first scenario, all visible pixels are black, indicating that there are no defects in the first case lead brick. In the second scenario, there are indications of defects at slices of 13 mm, 23 mm, 28 mm, and 37 mm, marked by white color. These slice depths were obtained from the previously conducted A-mode signal analysis. In the third scenario, almost the entire part of the third case lead brick has defects at a depth of 37 mm, as evidenced by the B-mode image showing evenly distributed white pixels in the image.